Editorial - RAMOS HOLGUÍN, BERTHA; Peñaloza Rallón, Anna Carolina (Universidad Pedagógica y Tecnológica de Colombia, 2020)
The editorial introduces the focus of the journal, the work of the authors, and food for thought for future publications.